Epidemiology and risk factors of diabetic retinopathy in upper Egypt: a 3-year prospective study - Hassan S. Yousef; Mohamed E. Ahmed; Esam A. G. Abu El Wafa; Mohamed A. K. Salih (Journal of the Egyptian Ophthalmological Society)
Objective To determine the prevalence and risk factors of diabetic retinopathy (DR) in adult diabetic patients during 3 years. Patients and methods This is a cross-sectional study that was carried out on the adult diabetic population who attended a large private referral ophthalmology center in Assiut City, Upper Egypt for 3 years. All cases were subjected to full history taking, ophthalmological examination, and dilated fundus examination for evidence of DR, and besides, the associated systemic complications were assessed. Results The study included a total of 2178 cases and the prevalence of DR was 18.2%. DR was more prevalent in females than males (67.9% vs. 32.1%). Also, DR was significantly associated with insulin use, moderate and poor control of diabetes mellitus, uncontrolled hypertension (HTN), dyslipidemia, and nephropathy (P<0.01 for all). The risk factors for DR were; older age (adjusted odds ratio (AOR) 1.69; 95% CI =0.91–1.97; P≤0.01), female sex (AOR 1.65; 95% CI =1.21–1.86; P =0.02), smoking (AOR 1.73; 95% CI =1.41–2.11; P =0.02), longer duration of DM (> 15 years) (AOR 2.87; 95% CI =2.48–3.29; P ≤0.01), insulin use (AOR 1.42; 95% CI =0.94–1.65; P=0.03), poor control of DM (AOR 3.98; 95% CI =3.69–5.41; P≤0.01), presence of HTN (AOR 2.62; 95% CI =2.37–2.89; P≤0.01) and dyslipidemia (AOR 1.65; 95% CI =1.42–2.02; P=0.03). Conclusion The prevalence of DR in adult diabetic patients was 18.2% and the significant risk factors for DR (arranged descendingly in power) were; poor control of DM, longer duration of DM (> 15 years), presence of HTN, smoking, high age, dyslipidemia, female sex, and insulin use.